Effects of exogenous plant hormones on sugar accumulation and related enzyme activities during the development of longan (Dimocarpus Longan Lour.) fruits. Issue 6 (2nd November 2019) - Tan, Si; Xie, Jianghui; Wang, Wei; Shi, Shengyou
ABSTRACT: Exogenous hormone treatment is a widely used and effective method to promote fruit ripening. To our knowledge, the effects of exogenous hormones on the sugar accumulation and related enzyme activities during the development of longan fruits have not yet been elucidated. In this study, the contents of sucrose, glucose and fructose, activities and transcriptional levels of sucrose phosphate synthase (SPS), sucrose synthase (SS), acid invertase (AI) and neutral invertase (NI) were detected during fruit development of exogenous hormone-treated and non-treated longan. The results indicated that exogenous hormones (IAA, ABA, GA3) could not alter the sugar contents when fruits were ripe but accelerate the sugar accumulation. IAA and ABA increased the gene transcriptional levels and enzyme activities of SS and SPS, and also showed the tendency of increasing the transcriptional levels and enzyme activity of AI. However, GA3 decreased the gene transcriptional levels of SS and SPS, and increased the gene transcriptional level of AI. Interestingly, GA3 also increased the enzyme activity of SPS which indicated GA3 may regulate the SPS activity at post-translational levels. Our results suggested that IAA, ABA and GA3 may regulate sugar accumulation during fruit development of longan.